Big Data for Big Decisions Building a Data-Driven Organization. - Pera, Krishna (Milton : Auerbach Publishers, Incorporated, 2022)
Building a data-driven organization (DDO) is an enterprise-wide initiative that may consume and lock up resources for the long term. Understandably, any organization considering such an initiative would insist on a roadmap and business case to be prepared and evaluated prior to approval. This book presents a step-by-step methodology in order to create a roadmap and business case, and provides a narration of the constraints and experiences of managers who have attempted the setting up of DDOs. The emphasis is on the big decisions - the key decisions that influence 90% of business outcomes - starting from decision first and reengineering the data to the decisions process-chain and data governance, so as to ensure the right data are available at the right time, every time. Investing in artificial intelligence and data-driven decision making are now being considered a survival necessity for organizations to stay competitive. While every enterprise aspires to become 100% data-driven and every Chief Information Officer (CIO) has a budget, Gartner estimates over 80% of all analytics projects fail to deliver intended value. Most CIOs think a data-driven organization is a distant dream, especially while they are still struggling to explain the value from analytics. They know a few isolated successes, or a one-time leveraging of big data for decision making does not make an organization data-driven. As of now, there is no precise definition for data-driven organization or what qualifies an organization to call itself data-driven. Given the hype in the market for big data, analytics and AI, every CIO has a budget for analytics, but very little clarity on where to begin or how to choose and prioritize the analytics projects. Most end up investing in a visualization platform like Tableau or QlikView, which in essence is an improved version of their BI dashboard that the organization had invested into not too long ago. The most important stakeholders, the decision-makers, are rarely kept in the loop while choosing analytics projects. This book provides a fail-safe methodology for assured success in deriving intended value from investments into analytics. It is a practitioners' handbook for creating a step-by-step transformational roadmap prioritizing the big data for the big decisions, the 10% of decisions that influence 90% of business outcomes, and delivering material improvements in the quality of decisions, as well as measurable value from analytics investments. The acid test for a data-driven organization is when all the big decisions, especially top-level strategic decisions, are taken based on data and not on the collective gut feeling of the decision makers in the organization.
5.2 The Lost Art of Decision-Making -- 5.3 Prioritizing Decisions: In Search of an Objective Methodology -- 5.4 Learning from the Bain Model -- 5.5 Decision Analysis -- 5.6 Decision Prioritization: Factors to Consider -- 5.7 Decision Prioritization: Creating a Process Framework -- 5.7.1 Cross-Dimensional Comparison -- 5.7.2 The Process Framework: Identifying and Prioritizing the "Big" Decisions -- Bibliography -- Chapter 6: Decisions to Data: Building a "Big" Decision Roadmap and Business Case -- 6.1 Toward a Data-Driven Organization: Building a "Big" Decision Roadmap
Description based upon print version of record.
6.1.1 Identifying and Prioritizing the Decisions
OCLC-licensed vendor bibliographic record.
Keywords: Organizational change; Business planning; Big data; Computer storage devices; BUSINESS & ECONOMICS / Management Science; COMPUTERS / Database Management / Data Mining; COMPUTERS / Information Technology